SHIFT IN ORIENTATION OF VOCATIONAL SCHOOL GRADUATES BASED ON LOCAL POTENTIAL FOR REGIONAL DEVELOPMENT - Lesmana, Widi (Universitas Negeri Semarang, 2018)
Indonesia has abundant natural and human potential. The development of vocational schools based on local potential is one of the efforts to prepare skilled labor to reduce the number of unemployed. This article aims to describe changes in orientation of vocational school graduates based on local potential for regional development. The method used is descriptive by examining 34 literacys relevant with research problems. The results of the study found that shifts in graduate orientation can be done by developing vocational schools based on local potential for regional development as preparation for skilled labor, vocational school graduates are projected to work in local and surrounding industries, entrepreneurial graduates are designed to open companies in their own or around so that the natural potential possessed by the local community is not beneficial to foreign parties. The development of vocational schools is carried out by identifying the characteristics of natural, cultural and artistic and technological potential in each region. Extensive natural potential analysis is carried out to determine priority potential so that it can be used as a reference in determining the spectrum of local potential-based expertise.